2009
DOI: 10.2478/v10078-09-0009-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Division II College Offensive and Defensive Football Players' Upper Body Strength Across One Repetition Maximum Test and The NFL-225 Test

Abstract: Comparison of Division II College Offensive and Defensive Football Players' Upper Body Strength Across One Repetition Maximum Test and The NFL-225 TestThe purpose of this study was to evaluate the effectiveness of predicting actual one repetition maximum (1RM) bench press strength from the National Football League (NFL) 225-test in college football players. Forty-one Division II college football players participated in this study. Participants' upper body strength scores were expressed relative to body weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…This study is believed to be the first to examine how the NFL-225 test relates to playing status between different positions in Division I college football players. The strong relationship between 1-RM bench press and the NFL-225 test is consistent with previous studies [4,10,31,32,[33][34][35][36][37][38][39][40]. These results indicate that higher levels of upper body strength likely contribute to achieving more repetitions in the NFL-225 test.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This study is believed to be the first to examine how the NFL-225 test relates to playing status between different positions in Division I college football players. The strong relationship between 1-RM bench press and the NFL-225 test is consistent with previous studies [4,10,31,32,[33][34][35][36][37][38][39][40]. These results indicate that higher levels of upper body strength likely contribute to achieving more repetitions in the NFL-225 test.…”
Section: Discussionsupporting
confidence: 91%
“…However, the physical skills required to be successful at one position are not necessarily the same for each position on the field. Previous research using physical performance measures has shown the presence of position specific skill requirements [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The research has commonly grouped liked positions (i.e., big skills = linemenoffensive and defensive, small skills = backsoffensive and defensive, mid skills = linebackers + tight ends).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation